PENGARUH PENYULUHAN MELALUI MEDIA VIDEO TERHADAP PENGETAHUAN DAN SIKAP GENETALIA HYGIENE REMAJA PUTERI SMP DWIJENDRA DENPASAR - Ni Nyoman Ayu Suci Marlina; Ni Wayan Suarniti; I Gusti Ayu Surati (Poltekkes Kemenkes Denpasar, 2021)
Genetalia hygiene is one of the efforts in personal hygiene that has an important role in the status of one's health behavior, to avoid interference with the reproductive organs.Genetalia hygiene is very important for woman because they tend to have urinary tract infection than man because they have shorter urination track. The purpose of this study was to determine the effect of counseling through media video on knowledge and attitudes about female adolescent hygiene genetalia at Dwijendra Junior High School Denpasar. This study uses a comparative analytic method with a one-group pre-test-post-test research design. The sample of this study was 80 and VIII grade students of Dwijendra Junior High School Denpasar with a total of 80 people. The sampling technique in this study is probability sampling. The instrument used was a questionnaire of 15 questions for knowledge, 10 questions about attitudes that have been valid and reliable. Data analysis techniques used paired T-Test. The results of the study for the average knowledge pre-test were 70.92 and the post-test knowledge after receiving counseling was 90.58 while the pre-test for attitude was 35.25 da post-test after the counseling was 43.64. Paired T-Test and Wilcoxon test results obtained p value = 0,000 0.05 These results indicate there is a significant influence on counseling through media video on knowledge and attitudes about female adolescent hygiene genetalia. The school is expected to increase health promotion.